Analysis on Gear Failure due to Electric Erosion - 潘紫微; 罗铭; 朱孝录 (Jixie chuandong)
This paper discusses the visible appearance and microscopical appearance characteristics of gear failure by electric erosion,including striped pattern,cloudy pattern,and riverside pattern.